The relationship between soybean (Glycine Max (L.) Merrill) seed quality and the response to molybdenum seed treatment - Bilbe, Sara Ann (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric.)--University of Stellenbosch, 2000.